IDENTIFIKASI MISKONSEPSI SISWA MENGGUNAKAN FOUR-TIER DIAGNOSTIC TEST PADA MATERI HUKUM TERMODINAMIKA DI SMA BONDOWOSO - Nita Dwi Handayani; Sri Astutik; Albertus Djoko Lesmono (FKIP Universitas Jember, 2018)
ABSTRACT The purpose of this research was to describe the misconception that studentsuse a Four-Tier Diagnostic Test on the material laws of thermodynamics inBondowoso High School. The population in this research is the entire class XI inSMAN 1 Tenggarang, SMAN 3 Bondowoso, and SMAN 1 Pujer. The selected samplesfor research was a class of XI MIPA2 SMAN 1 Tenggarang, XI MIPA2 SMAN 3Bondowoso, and XI MIPA1 SMAN 1 Pujer which is selected using the method ofpurposive sampling area. Data collection methods used in this research is a methodof documentation, tests, and interviews. The instruments used multiple choicediagnostic test shaped four levels and guidelines for interviews. Based on the resultsof data analysis and discussion can be known that overall misconception that studentson the subject of laws of thermodynamics in SMA Bondowoso of 28.04% so thisqualifies a misconception to low levels.Keywords: Misconception, Four-Tier Diagnostic Test, Laws Of Thermodynamics